Allergenic Can f 1 and its human homologue Lcn‐1 direct dendritic cells to induce divergent immune responses. Issue 10 (27th July 2015) - Posch, Beate; Irsara, Christian; Gamper, Fabian S.; Herrmann, Martin; Bindreither, Daniel; Fuchs, Dietmar; Reider, Norbert; Redl, Bernhard; Heufler, Christine
Abstract Why and when the immune system skews to Th2 mediated allergic immune responses is still poorly characterized. With two homologous lipocalins, the major respiratory dog allergen Can f 1 and the human endogenous, non‐allergenic Lipocalin‐1, we investigated their impact on human monocyte‐derived dendritic cells (DC). The two lipocalins had differential effects on DC according to their allergenic potential. Compared to Lipocalin‐1, Can f 1 persistently induced lower levels of the Th1 skewing maturation marker expression, tryptophan breakdown and interleukin (IL)‐12 production in DC. As a consequence, T cells stimulated by DC treated with Can f 1 produced more of the Th2 signature cytokine IL‐13 and lower levels of the Th1 signature cytokine interferon‐γ than T cells stimulated by Lipocalin‐1 treated DC. These data were partially verified by a second pair of homologous lipocalins, the cat allergen Fel d 4 and its putative human homologue major urinary protein. Our data indicate that the crosstalk of DC with lipocalins alone has the potential to direct the type of immune response to these particular antigens. A global gene expression analysis further supported these results and indicated significant differences in intracellular trafficking, sorting and antigen presentation pathways when comparing Can f 1 and Lipocalin‐1 stimulated DC. With this study we contribute to a better understanding of the induction phase of a Th2 immune response.